2018
DOI: 10.19080/jaicm.2018.06.555681
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Caudal Bupivacaine, Bupivacaine with Fentanyl and Bupivacaine with Tramadol Administration for Post Operative Analgesia in Children

Abstract: Objective: To compare the effectiveness of caudal bupivacaine, bupivacaine plus fentanyl and bupivacaine plus tramadol for post operative analgesia in children. Materials and methods:The study was conducted on 75 children of ASA I and II physical status aged 1 to 12 years undergoing elective infraumbilical surgeries. Patients were divided into 3 groups and the following were given in the caudal epidural space after the induction of anesthesia: a) Group I: 0.125% Inj. Bupivacaine 1ml/kg b) Group II: 0.125 Inj. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…In our study, nausea and vomiting were not present in any of the patients but reported in a study conducted by Khalid et al, [16] and Pavithra et al [17] may be due to the usage of increased dose of tramadol 2 mg/kg instead of 1 mg/kg as in our study.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…In our study, nausea and vomiting were not present in any of the patients but reported in a study conducted by Khalid et al, [16] and Pavithra et al [17] may be due to the usage of increased dose of tramadol 2 mg/kg instead of 1 mg/kg as in our study.…”
Section: Discussionsupporting
confidence: 43%
“…(2018) [17] as single-shot caudal epidural using 1 mL/kg of 0.25% bupivacaine alone Group 1 and 2 μg/kg fentanyl Group 2 or with 2 mg/kg tramadol Group 3 in 1-12 years old undergoing elective infraumbilical surgeries. Onset of pain is seen between 8 and 12 h in Group 3 as against 4-8 h in the other groups.…”
Section: Discussionmentioning
confidence: 99%
“…V, Ramani M, Bysani P & Srinivas D. analyzed Caudal Bupivacaine, Bupivacaine with Fentanyl & Bupivacaine with Tramadol for Post Usable Absense of pain. They close expansion of Tramadol to Bupivacaine gives drawn out & great quality post employable absense of pain in examination with Bupivacaine alone or with Fentanyl in Caudal Block in the post usable period 20. This concentrate somewhat upholds our review.…”
mentioning
confidence: 56%
“…2,3 There is plenty of literature regarding use of caudal epidural Bupivacaine for post-operative pain relief, but there is paucity of studies comparing Levo-Bupivacaine and Ropivacaine for pediatric caudal blocks. [7][8][9] Bupivacaine was introduced in 1963, is racemic mixture of R and S enantiomer, R-enantiomer of which is cardiotoxic. The drug also has neurotoxicity and residual motor block effects.…”
Section: Introductionmentioning
confidence: 99%